2007
DOI: 10.4049/jimmunol.179.6.3973
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD8 T Cells against a Novel Epitope in TB10.4: Correlation with Mycobacterial Virulence and the Presence of a Functional Region of Difference-1

Abstract: Although infection with Mycobacterium tuberculosis (M.tb) induces a robust CD8 T cell response, the role of CD8 T cells in the defense against M.tb, and the mechanisms behind the induction of CD8 T cells, is still not clear. TB10.4 is a recently described Ag that is expressed by both bacillus Calmette-Guérin (BCG) and M.tb. In the present study, we describe a novel CD8 T cell epitope in TB10.4, TB10.43-11. We show that TB10.43-11-specific CD8 T cells are induced at the onset of infection and are present throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 46 publications
(175 reference statements)
6
91
0
Order By: Relevance
“…administration of BCG at high doses ($1 Â 10 6 CFU/mouse), which does give a significant CD8 response specific for TB10.4) (Fig. 2) [15,24,25]. The recombinant BCG::RD1-strain expressing the ESAT-6 secretion system showed similar TB10.4 epitope recognition patterns as virulent M.tb, both recognizing the MHC-I restricted epitopes in P1 and P2 and the MHC-II restricted epitope in P8 (data not shown), corresponding to earlier described epitopes [24,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…administration of BCG at high doses ($1 Â 10 6 CFU/mouse), which does give a significant CD8 response specific for TB10.4) (Fig. 2) [15,24,25]. The recombinant BCG::RD1-strain expressing the ESAT-6 secretion system showed similar TB10.4 epitope recognition patterns as virulent M.tb, both recognizing the MHC-I restricted epitopes in P1 and P2 and the MHC-II restricted epitope in P8 (data not shown), corresponding to earlier described epitopes [24,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…2) [15,24,25]. The recombinant BCG::RD1-strain expressing the ESAT-6 secretion system showed similar TB10.4 epitope recognition patterns as virulent M.tb, both recognizing the MHC-I restricted epitopes in P1 and P2 and the MHC-II restricted epitope in P8 (data not shown), corresponding to earlier described epitopes [24,26,27]. As it has been suggested that the RD1 region enables M.tb to escape the phagosome [28], it could be speculated that altered intracellular trafficking of BCG might lead to a different epitope pattern and/ or to new protective epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, flow cytometry evaluation of cytokine secretion profiles and cell surface phenotypes of peripheral blood T cells have been employed in the attempt to differentiate active and latent TB infection [ 5,11,12 ]. A large body of evidence suggests the important contribution of CD8 T cells in the MTB-specific immune response [6][7][8]13 ]. The latter display specific effector functions performed upon recognition of mycobacterial antigens -production of IFN-γ, lysis of infected host cells, and direct killing of MT bacteria [ 14 ].…”
mentioning
confidence: 99%